Detection of ICT-based Border between Indonesia and Singapore - Danny , F.; Dewi, H. C.; Febi, N. B.; Aprillia, D. P.; Goan, G. H.; Julie , N. C.; Gustini, W.; Alia , A. (Novel Perspectives of Geography, Environment and Earth Sciences Vol. 1, 2022)
This study seeks to show maritime aspects and shipbuilding technology and their relationship with social society through transnational concepts. With globalization, and to develop networks, people really need sea transportation to support the transnational process. The Chinese population of Batam, a community group in the city of Batam, cannot be separated from the high intensity of transportation between Batam and Singapore. Since they migrated by boat from the Chinese mainland, the Batam Chinese have existed on the island for centuries. Because of their perseverance, social networks, and proximity to Singapore, Batam Chinese have dominated the local economy. The transnational concept is a form of social network. In this case, transnationalism is seen as a social network between Chinese in Batam and Singapore. The relation between Batam and Singapore covers many sectors, including tradition, economy, trade, and other social activities. In the tradition of transnational network between China and Batam in terms of Chinese temples, the Chinese’ transnational temple network interlinks all temples in the foreign countries and in China itself.